The safety net role of inland fishing in the subsistence strategy of multi-active forest dwellers in southern Cameroon - Edmond Dounias; Serge Cogels; Serges Mvé Mbida; Stéphanie Carrière (Revue d'ethnoécologie)
The Mvae and the Ntumu, two African rainforest ethnic groups belonging to same Fang linguistic sub-group, live together as good neighbors in the Ntem watershed of southern Cameroon. Like most forest dwellers in the Congo Basin, these two societies have implemented a multi-active type of subsistence economy: hunting, trapping, gathering and fishing are practiced in addition to a predominant slash-and-burn agriculture. The aim of this paper is to emphasize that these ethnic groups, which do not have fishery as their most salient production domain, have nevertheless acquired a remarkable expertise in wild fishery, notably through a diversity of techniques and socio-ecological conditions of practice. The sizable variety of fishing methods takes advantage of the great vascularity of the hydrographic network and involves in a complementary way all the members of the community — young and old, of both genders, in solo, in pairs or in larger groups of participants. This large range of possibilities ensures a continuous provision of fish over the year and establishes inland capture fishery as a real safety net that can provide — in all circumstances and in sufficient quantities — resources that are culturally valued, that are an appreciable extra-source of income, and whose nutritional role is acknowledged. Despite of being the pervasive basis of the subsistence economy of forest peoples in Central Africa, the contribution of inland capture fishery to the livelihoods of Congo basin forest dwellers remains unobtrusive and is overlooked by development agencies.